Do Types of Employment Matter in Explaining Juvenile Delinquency? A Longitudinal Study of South Korean Youth - Lee, Hee-Jung (Criminal justice and behavior, 2018)
This study examines the effects of job type on crime and substance use. The longitudinal panel data from the Korean Youth Panel Survey conducted by the National Youth Policy Institute are utilized to explore this question. Results from the fixed effects models show that a job status change from nonworker to worker holding an informal job increases the chance of participating in crime and substance use. Interestingly, a job status change from nonworker to worker holding a formal job is not associated with an involvement in crime and delinquency. In addition, it shows that the effects of job type on crime and delinquency are not varied by gender except for an intensive female worker who holds a formal job.